DAMPAK BERMAIN GAME ONLINE MOBILE LEGENDS TERHADAP PERILAKU TOXIC REMAJA - Rio Aditya Saputra; Hadi Pranoto; Tri Anjar (Universitas Muhammadiyah Metro, 2026)
The purpose of this study was to determine the impact of playing mobile legends online games on the toxic behavior of adolescents in Sukaraja Nuban Village, Batanghari Nuban District, East Lampung Regency. The research method used is descriptive qualitative. Researchers intervene directly in collecting and analyzing the results obtained. The research instruments used are observation and interviews. The interview used was an unstructured interview. The results of the study found that toxic behavior is divided into two, namely toxic gameplay behavior and abusive communication to other players. All teenagers interviewed performed toxic behavior when playing mobile legends online games.